Treatment of Landfill Leachate with Fenton's Reaction - Xiang, Xinyi; Zheng, Huaili; Chen, Lei; Chen, Jie; Zhu, Guocheng (Asian Journal of Chemistry, 2013)
In this study, Fenton's reaction was used in landfill leachate treatment, aiming to find a convenient and flexible way for the treatment of such kind of high-concentration organic wastewater. COD and absorbance of UV254 were selected as the main water quality indicators for landfill leachate. pH value (6) and Fe2+/H2O2 (10) ratio were tested to obtained the optimum condition, based on which, a series of comprehensive experiments were carried out for proof-checking. It was found that the Fenton's process had effect in real landfill leachate treatment. By controlling reaction condition, the removal of COD and UV254 reduction can be above 40 %, which indicated Fenton's process can be used as an effective pretreatment or post-treatment method for high-concentration organic wastewater.